The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s10067-014-2639-6
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association of vitamin D receptor gene polymorphisms/haplotypes in Sjögren’s syndrome

Abstract: syndrome. In the current study, 105 patients with pSS and 93 healthy controls were tested for VDR gene polymorphisms (BsmI, ApaI, TaqI and FokI) genotypes. There were no statistical differences in the distribution of BsmI, TaqI, ApaI and FokI genotypes and the common haplotypes between pSS patients and healthy controls. We hypothesized that the TaqI, BsmI, ApaI, and FokI polymorphisms of the VDR gene are not associated with the development of primary Sjögren's syndrome in the Hungarian population studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 26 publications
0
7
0
2
Order By: Relevance
“…Similarly, in two other studies comparing patients with SS and healthy controls, no difference in vitamin D levels was noted . Also, one study could not find any associations between vitamin D receptor gene polymorphisms/haplotypes and SS . With regard to disease manifestations, one study reported low levels of vitamin D in patients with SS presenting with peripheral neuropathy or with lymphoma compared to patients without these manifestations .…”
Section: Biological Factorsmentioning
confidence: 93%
“…Similarly, in two other studies comparing patients with SS and healthy controls, no difference in vitamin D levels was noted . Also, one study could not find any associations between vitamin D receptor gene polymorphisms/haplotypes and SS . With regard to disease manifestations, one study reported low levels of vitamin D in patients with SS presenting with peripheral neuropathy or with lymphoma compared to patients without these manifestations .…”
Section: Biological Factorsmentioning
confidence: 93%
“…It is known that the VDR gene is situated on chromosome 12 (12q12-q14). It has numerous single nucleotide polymorphisms (SNPs) (gene polymorphisms sites) and expresses a ligand-activated transcription factor [33,34]. Some of these SNPs play critical roles in the modification of 1,25-dihydroxyvitamin D uptake [17] and can promote vitamin D function and metabolism [33].…”
Section: Vitamin D and Genetic Variancesmentioning
confidence: 99%
“…In contrast, Agmon-Levin et al [61] found no difference in serum 25(OH)D between SS patients and controls, although levels were lower in patients with peripheral neuropathy (18.6 vs 22.6 ng/ml) or lymphoma (13.2 vs 22.0 ng/ml). Furthermore, there is no evidence that genetic polymorphisms in the vitamin D pathway associate with the prevalence or severity of SS [62]. No studies have investigated the effect of vitamin D treatment in SS.…”
Section: Ssmentioning
confidence: 99%